Potentially applicable bioremediation mechanisms for metal‑tolerant bacteria from industrial waste electroplating - Alhammadi, E.; Halimoon, Normala; W. Johari, W. L.; Zulkeflee, Z. (Springer, 2023)
Metallic pollution in aquatic ecosystems has expanded dramatically due to the astonishing growth in industrial activity, posing a threat to the safety and health of the environment. Bacterial bioremediation offers promising solutions for decontaminating a polluted environment in a variety of situations. As a result, the tolerance and toxicity levels of the quaternary metal in bacteria isolated from the electroplating effluent were evaluated. The best tolerable strains were Bacillus megaterium, Sphingobacterium ginsenosidimutans, and Kocuria rhizophila, chosen for potential biosorption and bioaccumulation at high concentrations and maximum sorption rate and time. The mechanisms of bioremediation were verified by Scanning electron microscopy energy-dispersive x-ray analysis and Fourier transform infrared spectroscopy. The results showed that the maximum biosorption was 83.73% Ni and 75.49% quaternary during 6 h, while the Cu and Ni accumulation levels were 0.291 mg/g at 24 h and 0.159 mg/g at 12 h in B. megaterium,, respectively. The consortium achieved high biosorption with individual metals and quaternary ranging from 75.68 to 90.79%, and the highest accumulating amount of Cu was 0.399 mg/g during 12 h and 0.374 mg/g Ni during 6 h. During the exponential phase and using the bacterial consortium, the best metal bioremediation outcomes were found. It was observed that metal binding changes cell morphology and FTIR spectra identified the dominant groups involved in the biosorption of metals on the surfaces of bacteria. The study shed some light and offered more knowledge of the interactions of metal-tolerant bacteria during bioremediation processes and their practical applicability to mineral processing.